Experimental Study on Two-Step Concrete Corbels with Several Interface Conditions - Mohamed A. Hassan; M. Nasser Darwish; Said M. Allam; Muhammad A. Diab (Advances in Civil Engineering)
Corbels are usually used in precast concrete structures for beam–column connections and are common in industrial structures to support crane girders and may be required in new alteration works. To overcome the difficulty of casting columns with corbels, especially in precast concrete industry, columns are sometimes cast without their corbels, and then corbels are cast in a following step. Sometimes, new corbels get added to existing columns to support new crane girders. Thus, two-step corbels may be installed using different techniques depending on several criteria, and several factors affect their behavior, some of which mainly the interface conditions are experimentally investigated. One control specimen with a monolithic corbel and five two-step corbel specimens were tested. The mean roughness depth of the column–corbel interface varied between 4 and 8 mm. Moreover, using adhesive components on the hardened column–corbel interface was investigated. Besides, steel reinforcement implantation was attempted and studied for corbels with or without horizontal stirrups. For the tested cases, results show that two-step corbels can be a good replacement to monolithic corbels and can achieve up to 92% of the monolithic corbels capacity. Increasing the mean roughness interface depth between corbels and column slightly increased the two-step corbel capacity and improved its behavior. Using adhesive epoxy to the column–corbel interface can achieve the behavior and ultimate load capacity of two-step corbel with mean roughness depth of 4 mm. Implanting corbels’ reinforcement is not recommended unless specific precautions and measures are assured and the embedment depth should be calculated and implemented to accommodate all expected failure mechanisms.